South Africa : 2009 Article IV Consultation; Staff Report; Staff Statement and Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for South Africa. (IMF Staff Country Reports; Country Report ;, 2009)
The major risk factors faced by the Isle of Man (IOM), which have been given prominence by the global financial crisis, relate to large exposures toward parent banks. The recent global financial markets turmoil has had a significant impact on the Manx financial system. The paper also presents a detailed assessment of IOM's Observance of the Basel Core Principles for Effective Banking Supervision Report. The Financial Supervision Commission has adequate power to ensure compliance with its regulations and other orders, and it uses power when the occasion demands.